Enhanced activity of macrophage M1/M2 phenotypes in periodontitis - Yang, Jingmei; Zhu, Yan; Duan, Dingyu; Wang, Panpan; Xin, Yuejiao; Bai, Lin; Liu, Yiying; Xu, Yi (Archives of oral biology, 2018)
•In this study, we are the first one to find that the ratio of M1/M2 was significant higher in periodontitis group compared with that in gingivitis one.•In addition, the relative expressions of IL-1β and MMP-9 also increased in periodontitis group and was correlated with the ratios of M1/M2.•PD was positively correlated with ratios of M1/M2.•Therefore, analysis of M1/M2 ratio may provide us useful information on the periodontal health status. Monocytes/macrophages play a key role in mobilizing host defense against microbial infection. The selectivity of gene expression can turn macrophages into M1- or M2-type and the plasticity and differentiation of both M1 and M2 macrophages may play important roles in the development of periodontal disease. Our research aimed to study the association between the ratio of M1/M2 macrophage and inflammatory cytokines IL-1β, MMP-9, and investigate the expressions of M1-and M2-type macrophages in gingivitis and chronic periodontitis. Forty specimens were collected from gingivitis individuals (n=20) and chronic periodontitis (n=20). Probing depth (PD), clinical attachment level (CAL), plaque index (PI) and bleeding on probing (BOP) were recorded. The expressions of M1- and M2-type macrophages are detected with immunohistochemical method and the relative expressions of M1-, M2-type macrophage, IL-1β and MMP-9 were assayed using real-time polymerase chain reactions. The M1 and M2 peptide were mainly observed in the cytoplasm of gingival connective tissue. The ratio of M1/M2 was significant higher in chronic periodontitis group compared with that in gingivitis one. In addition, the relative expressions of IL-1β and MMP-9 also increased in periodontitis group and was correlated with the ratios of M1/M2. Meanwhile, PD was positively correlated with ratios of M1/M2. Periodontal inflammation associates with an enhancement of ratio of M1/M2 phenotypes of macrophages. M1/M2 ratio could provide useful information on the periodontal tissue health status.